Predicting Group II pulmonary hypertension: diagnostic accuracy of the H2FPEF and OPTICS scores in Scotland. Issue 1 (27th April 2022) - Stubbs, Harrison; MacLellan, Alexander; McGettrick, Michael; Jani, Bhautesh; Brewis, Melanie; Church, Colin; Johnson, Martin
Abstract : Objective: Group II pulmonary hypertension (PH) can be challenging to distinguish from Group I PH without proceeding to right heart catheterisation (RHC). The diagnostic accuracy of the H2FPEF and OPTICS scores was investigated in Scotland. Methods: Patients were included in the study if they were referred to the Scottish Pulmonary Vascular Unit between 2016 and 2020 and subsequently diagnosed with Group II PH or Group I PH which was either idiopathic, heritable or pulmonary veno-occlusive disease. The established cut offs for the H2FPEF and for the OPTICS scores were applied retrospectively to predict the presence of Group II PH. The diagnosis from the scores were compared with the MDT consensus diagnosis following RHC. Results: 107 patients with Group I PH and 86 patients with Group II PH were included. Retrospective application of the OPTICS score demonstrated that pretest scoring would detect 28% of cases with Group II PH yet at the cost of misdiagnosing 4% of patients with Group I as Group II PH (specificity 0.96). The H2FPEF score had a far greater sensitivity (0.70) yet reduced specificity (0.91), leading to misdiagnosis of 9% of Group I PH cases. Conclusion: While the specificity of these scores was high, the lack of perfect specificity limits their utility as it results in missed patients with Group I PH. As a consequence, they cannot replace RHC as the means of diagnosing the aetiology of PH in their current form. The scores may still be used to support clinical judgement or to indicate the advisability for further provocative testing at RHC.